TEACHERS’ STRATEGIES IN TEACHING ENGLISH DURING PANDEMIC COVID-19 - Jumrah AM Parusi; Mawardin M. Said; Mashuri Mashuri (Tadulako University, 2022)
At the end of 2019, the world was shocked by the Covid-19 virus in Wuhan, China. This situation requires teaching and learning activities to be carried out at home. This research aims to find out the teachers’ strategies in teaching English during Pandemic Covid-19 at SMP Islam Terpadu Qurrata 'Ayun Palu. This research used qualitative descriptive method. Data collection was carried out with questionnaire and recorded interview procedure. The subjects of the research were two English teachers. Based on the results of the research, the researcher can draw the conclusion that the strategies used by teachers are first is communicative language teaching and many types of applications, second is class management. The strategies used by teachers were quite effective and increased students' interest in learning, so that students are motivated to learn English during the pandemic.